Collective bargaining in Western Europe, 1995-1996 - Fajertag, Giuseppe; European Trade Union Institute (ETUI) (Brussels : ETUI, 1996)
Bibliotheek François Vercammen
Engels
Monografie
Keywords: arbeidsverhoudingen; Europese Unie (EU).; West-Europa.